Uniformed Protest, Unruly Dissent: Roses, Discord, and Tear Gas in Indonesia, Nepal, and Serbia - Rahmat AP, Surfian; Hady, Ahmad Prasetya (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
The phenomenon of secondary school students’ involvement in political protests in Indonesia, Nepal, and Serbia during August–September 2025 emerged almost simultaneously, yet exhibited divergent patterns of mobilization. At the same time, scholarship on social movements has remained dominated by studies of university students, while secondary students are often relegated to the margins, with virtually no cross-national comparative analyses available. This study aims to compare forms of solidarity, agency, and institutional support surrounding students in the three cases by integrating the perspectives of Political Opportunity Structure (POS) and structuralism. Methodologically, the research employs a comparative study based on scholarly literature, media reports, and relevant academic documents. The findings reveal that Nepal demonstrates generational solidarity that fosters transformative agency; Serbia illustrates institutional solidarity that generates moral agency; whereas Indonesia operates within a structural vacuum, producing only a fragile form of pseudo-agency. These variations are further shaped by historical trajectories, economic inequalities, educational institutions, political culture, and geographic conditions. The study underscores that student agency is relational, constituted through the interplay between external political opportunities and the availability of internal structural supports. Normatively, the findings suggest that when students receive institutional backing or inclusive spaces for participation, they can function as moral and political agents reinforcing state accountability. Conversely, state repression does not produce uniform outcomes: in Serbia, repression strengthened moral consolidation through symbolic peaceful acts; in Nepal, state pressure fueled coordinated radical escalation; while in Indonesia, repression accelerated fragmentation, rendering student protests fragile, anarchic, and vulnerable to manipulation.